Anti‐D prophylaxis: past, present and future. Issue 1 (February 2014) - de Haas, M.; Finning, K.; Massey, E.; Roberts, D. J.
SUMMARY The new British Committee for Standards in Haematology (BCSH) guidelines for the use of anti‐D immunoglobulin in pregnancy provide a welcome clarification of the use of anti‐D in ectopic pregnancy and after red cell salvage during caesarean section, of dosing with different preparations and distinguishing non‐immune and immune anti‐D. The routine use of anti‐D prophylaxis (RAADP) to prevent Rhesus (Rh) D alloimmunisation during the third trimester is well established and requires careful and well‐audited local implementation to achieve the maximum public health benefit. In the UK, such scrutiny may be provided by the reporting of failed anti‐D prophylaxis at women who have produced an immune anti‐D that is detectable for the first time in the current pregnancy through the voluntary Serious Hazards of Transfusion reporting scheme (SHOT). Application of fetal RHD genotyping would avoid giving anti‐D to RhD negative women carrying an RhD negative fetus. RAADP is directed by fetal RHD genotyping in some countries in Northern Europe led by the Netherlands and Denmark. The economic case for RAADP directed by fetal RHD genotyping needs to be carefully evaluated and in England is under consideration by National Institute for Health and Clinical Excellence (NICE). Possible future developments include the use of monoclonal anti‐D preparations, now in advanced clinical trials, and also testing the hypothesis that directed RAADP from early in the second trimester may further reduce anti‐D immunisation.